2019
DOI: 10.1186/s13063-019-3943-x
|View full text |Cite
|
Sign up to set email alerts
|

Using an incentive spirometer reduces pulmonary complications in patients with traumatic rib fractures: a randomized controlled trial

Abstract: BackgroundAn incentive spirometer (IS) is a mechanical device that promotes lung expansion. It is commonly used to prevent postoperative lung atelectasis and decrease pulmonary complications after cardiac, lung, or abdominal surgery. This study explored its effect on lung function and pulmonary complication rates in patients with rib fractures.MethodsBetween June 2014 and May 2017, 50 adult patients with traumatic rib fractures were prospectively investigated. Patients who were unconscious, had a history of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 36 publications
(30 reference statements)
3
49
0
7
Order By: Relevance
“…Several studies have reported similar profile in rib fracture patients receiving conservative treatment. 26,27…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported similar profile in rib fracture patients receiving conservative treatment. 26,27…”
Section: Discussionmentioning
confidence: 99%
“…This maneuver emphasizes lung inflation, increasing tidal volume, and maintaining patency of the smaller airway [8]. Like other prophylactic measures, such as smoking cessation, administration of antibiotics, bronchodilators, and chest physical therapy, incentive spirometer has been shown to decrease the rate of postoperative lung atelectasis and decrease pulmonary complications after cardiac, lung, or abdominal surgery [8]. It also reduced pulmonary complications, and improved pulmonary function test (PFT) results in patients with rib fractures [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…It encourages deep inspiratory and expiratory breathing by having the patient take long, deep breaths with subsequent pauses. This maneuver emphasizes lung inflation, increasing tidal volume, and maintaining patency of the smaller airway [ 8 ]. Like other prophylactic measures, such as smoking cessation, administration of antibiotics, bronchodilators, and chest physical therapy, incentive spirometer has been shown to decrease the rate of postoperative lung atelectasis and decrease pulmonary complications after cardiac, lung, or abdominal surgery [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kemampuan cough atau batuk yang menurun juga merupakan salah satu penyebab ARDS. [5][6][7][8] Pain, incentive spirometry, cough (PIC core) secara original yang dibuat oleh Wellspan York Hospital, York, Pennsylvania, USA digunakan untuk mengevaluasi dan memonitor pasien selama perawatan. 9 Berdasarkan latar belakang yang telah dipaparkan maka dilakukan penelitian ini yang bertujuan untuk menilai spesifisitas dan sensitivitas PIC score dalam memrediksi terjadinya ARDS pada pasien patah tulang iga akibat trauma tumpul toraks.…”
Section: Pendahuluanunclassified